Outcomes of Osteomyelitis in Patients with Diabetes: Conservative vs. Combined Surgical Management in a Community Hospital in Puerto Rico - Maldonado, Miguel; Cajigas-Feliciano, Yanniris; Torres-Torres, Nancy (Puerto Rico Health Sciences Journal, 2011)
Objective: Diabetes predisposes patients to multiple complications, such as osteomyelitis, which, if not managed adequately, may result in amputation, sepsis, or death. This study aimed to compare the rates of amputation associated with two different treatment plans for osteomyelitis being utilized with a group of Puerto Ricans with diabetes. Methods: We reviewed the medical records of adult patients with diabetes and osteomyelitis who had been admitted to a community hospital within a two-year timeframe; a total of 169 records were reviewed. Data were analyzed using descriptive statistics, chi-square, odds ratios, and multivariate logistic regression to compare the amputation rate of patients receiving conservative management (antibiotics and/or local care alone) with that of patients receiving combined surgical treatment (any modality consisting of an initial surgical treatment plus antibiotics and/or local care). Results: We found a general amputation rate of 34.5%. Amputation was less likely in patients undergoing combined surgical treatment (OR: 0.22; 95% IC: 0.08-0.59) than it was in those patients whose disease management was conservative. In addition, men (OR: 2.09; 95% CI: 1.04-4.23) and non-geriatric patients (OR: 3.38; 95% CI: 1.65-6.94) had higher probabilities of amputation than did women and geriatric patients, respectively. Conclusion: This study revealed an amputation rate among patients with diabetes that is higher than that reported in the United States (34.5% vs. 11.0% to 20.0%). We also found that the probability of amputation secondary to osteomyelitis among patients with diabetes is two times higher for men and three times higher for non-geriatric patients; combined surgical treatment was associated with a significant reduction (78%) of the probability of amputation.